EVALUATION OF SEXUAL PERFORMANCE IN WOMEN TREATED FOR BREAST CANCER - Sposito, Letícia; Vitorino, Caroline Nakano; Bortolotti, Gislaine Maria Fontanetti; Motoki, Andre Hideo; Buttros, Daniel de Araújo Brito (Mastology, 2020)
Objective: To assess the sexual performance (SP) pattern in women treated for breast cancer (BC). Methods: Cross-sectional study with 33 women treated for BC. We included women aged between 35 and 66 years, with histopathological diagnosis of breast cancer, who already concluded the initial oncological treatment (surgery, chemotherapy and radiotherapy), in stage IV, assisted in the Unified Health System. They signed the informed consent form. Oncological data, such as staging, type of surgery, type of adjuvant treatment and follow-up time were collected through the analysis of medical records. The women were submitted to individual interview to assess SP, and the Female Sexual Quotient (FSQ) questionnaire was applied. The FSQ is formed by 10 objective questions that score from 0 to 5 points according to the answer: never, infrequently or rarely, sometimes, nearly 50% of the time, most of the time, always. The final score is defined by the sum of points multiplied by 2, and the SP is classified as: poor (0-20), unfavorable (22-40), fair (42-60), good (62-80), and excellent (82-100). Mean/standard deviation and percentage rates were used for statistical analysis. The study was approved by the Research Ethics Committee, Plataforma Brasil/CAAE: 02241618.1.0000.5381. Results: The mean age and oncological follow-up were 55±11 years and 4.5±2 years, respectively. The most prevalent oncological data were: 35% were in stage 2; 84% were submitted to conserving surgery; 95%, to radiotherapy; 65% underwent chemotherapy; and 80% were on endocrine therapy. Regarding sexual performance, 62% spontaneously think about sex; 35% are always interested in sex; and 54% are always stimulated by the “foreplay”. During the sexual relation, 32% always get lubricated; 45% become more stimulated when the partner is aroused; 45% always relax their vagina appropriately; 45% never feel pain; 52% always get involved without distraction; 51% always reach orgasm; and 42% always wish to repeat sexual relations in the following days. After calculating the final score, the conclusion was that 6% have poor sexual performance; 20%, unfavorable; 20%, fair; 38%, good; and 16%, excellent. Conclusion: Most women treated for breast cancer present with sexual performance classified between good and excellent, according to the Female Sexual Quotient.